Book Reviews (The Muslim world, 1954)
Book reviewed in this article: The Christian Attitude to Other Religions, By E. C. Dewick Introduction to the Qur'n, By Richard Bell The Shl'a of India. By John Norman Hollister, Ph. D. Modern Lebanese Proverbs, Collected at Ras al-Matn Allamatnf al-Hayat. Edited by Dr. Ahmad Amn Among Arabic Manuscripts, Memories of Libraries and Men. By I. Y. Kratch-kovsky Rebirth and Destiny of Israel. By David Ben Gurion An Introduction to the Study of Contemporary Iraq By Zaki Salih The Islamic State and Other Political Essays. By Ajit Kumar Sen